Application of the Jigsaw Technique to Enhance Student Motivation and Engagement in Vocabulary Learning - Afandi, Mujad Didien; Zaniar, Savira; Shari, Destita; Aquariza, Novi Rahmania; Basuki, Edi Pujo (Indonesia Berdaya, 2025)
Traditional methods such as rote memorization and one-way instruction lead to low interest and limited interaction. The community service program introduced the cooperative jigsaw method, where students worked in small groups, took responsibility for vocabulary learning, and taught peers collaboratively. This program aimed to enhance student motivation and engagement in English vocabulary learning through the jigsaw technique at a primary school in Pranti Village, Sedati, Sidoarjo. Using observation checklists, questionnaires, and classroom documentation, the study found that students were attentive, participative, focused, and confident, showing initiative and effective interaction with peers and media. Questionnaire results confirmed increased motivation, enjoyment of responsibility, reduced stress, and higher confidence when learning collaboratively. Key supporting factors included engaging media, peer collaboration, student autonomy, and the teacher’s role as facilitator, aligning with Self-Determination Theory. In conclusion, the jigsaw technique effectively improved both motivation and engagement in vocabulary learning, offering a dynamic, student-centered approach that fosters meaningful and enjoyable language learning for young learners.